BENTUK SENGKETA EKONOMI SYARIAH DAN PENYELESAIANNYA - Hendra Pertaminawati (Sekolah Tinggi Agama Islam Indonesia Jakarta, 2019)
Disputes in sharia economists can be in the form of defaults (broken promises) where a condition which due to negligence cannot meet the achievements specified in the agreement and Acts against the Law, Every act that violates the law, which brings harm to others, obliges the person who due to the wrong issue a loss that, compensate for these losses. Sharia Economic Dispute Settlement can be carried out by deliberation, mediation or by the court